Pengaruh Pendapatan Negara dan Pengeluaran Pemerintah Terhadap Laju Pertumbuhan Ekonomi Nasional Paska Covid-19 - Putri, Indah Ameylia; Mutiarin, Dyah; Saputro, Muhammad Noor Cahyadi Eko (Prosiding University Research Colloquium, 2023)
A country’s economic growth inevitably evolves from one era to the next. But in general, the global geopolitical conditions that exist in the 21st century era have affected the structure of government revenues and expenditures. This study will discuss the effect of state revenues and government expenditures that affect the rate of national economic growth after the co-19 pandemic. This study uses a systematic literature review analysis method obtained through various academic and non-academic articles such as journal articles, policy briefs, national development planning documents, working papers of relevant ministries, and mainstream online mass media on national economic conditions. The results in this study prove that national economic development after the co-19 pandemic is the result of restructuring the government’s ability to manage state finances which include revenue generation and spending. In addition, the state’s ability to manage large production capacity can be a sign of the high level of prosperity of citizens in a nation. So this research has broad consensus implications characterized by incessant investment in human capital and physical infrastructure that can later accelerate the rate of economic growth.